Ceftazidime-Avibactam as Osteomyelitis Therapy: A Miniseries and Review of the Literature - Alessandro Mancuso; Luca Pipitò; Raffaella Rubino; Salvatore Antonino Distefano; Donatella Mangione; Antonio Cascio (MDPI AG, 2023)
Bone and joint infections (BJIs) caused by multidrug-resistant gram-negative bacteria are becoming a concern due to limited therapeutic options. Although not approved for these indications, an ever-growing amount of evidence supports the efficacy and safety of ceftazidime-avibactam as a therapy for osteomyelitis and prosthetic joint infections. Here, we present three cases of difficult-to-treat resistant Pseudomonas aeruginosa osteomyelitis that were successfully treated with ceftazidime-avibactam alone or in combination therapy with fosfomycin and amikacin. Ceftazidime-avibactam was prescribed at a daily dose of 2.5 g every 8 h for 42 days in all cases. One potential drug-related adverse effect was observed, i.e., Clostridioides difficile infection, which occurred after fourteen days of treatment with ceftazidime-avibactam.